2009
DOI: 10.1017/s1368980008004412
|View full text |Cite
|
Sign up to set email alerts
|

Maternal perceptions of their child’s weight status: the GENESIS study

Abstract: Objective: The objective of the present work was to quantify mothers' misclassification of pre-school children's weight status and to determine factors associated with the maternal misperception. Design: A representative sample of 2287 children aged 2-5 years was examined (GENESIS study). Mothers' perceptions of their child's weight status and the children's and mothers' anthropometric and other characteristics (sociodemographic and lifestyle) were recorded. Results: Almost 38 % of mothers underestimated their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
77
9
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 36 publications
9
77
9
5
Order By: Relevance
“…Boys themselves and parents of boys tended to underestimate to a higher extent boys' increased body weight compared with girls and parents of girls, respectively. This finding is in accordance with previous findings (9,32,35) and is usually explained by the fact that female adolescents are more concerned with their body image than male adolescents, enabling girls to more correctly classify themselves based on their weight status (36) . On the other hand, parents often explain body size differences between girls and boys as normal gender differences and in this context they also may be influenced by the social desirability for a lower body weight in girls and for a larger body size in boys.…”
Section: Discussionsupporting
confidence: 93%
“…Boys themselves and parents of boys tended to underestimate to a higher extent boys' increased body weight compared with girls and parents of girls, respectively. This finding is in accordance with previous findings (9,32,35) and is usually explained by the fact that female adolescents are more concerned with their body image than male adolescents, enabling girls to more correctly classify themselves based on their weight status (36) . On the other hand, parents often explain body size differences between girls and boys as normal gender differences and in this context they also may be influenced by the social desirability for a lower body weight in girls and for a larger body size in boys.…”
Section: Discussionsupporting
confidence: 93%
“…In our LSES group, children's OWOB was strongly associated with maternal underestimation of child's weight status, a finding consistent with those in other populations (Maynard et al, 2003;Carnell et al, 2005;Manios et al, 2009). More than half of the mothers underestimated their children's weight status, and the rate of underestimation was higher among mothers of OWOB children.…”
Section: Discussionsupporting
confidence: 90%
“…The sample size calculation assumed a prevalence of 25% OWOB among the children. Previous data have indicated that the prevalence of the exposure variable (maternal underestimation of children's weight) among mothers of overweight children is 0.5 (Maynard et al, 2003;Manios et al, 2009). If the true odds ratio for OWOB in exposed subjects relative to unexposed subjects were 2.5, a sample size of 211 would allow the detection of an odds ratio of this magnitude, with 80% power in a two-sided test with Type I error set to 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If overweight is recognised early in life, prevention and treatment strategies are more likely to be successful. 14,15 On the other hand, maternal underestimation of their child's weight may promote an unfavourable weight gain, in both normal-weight children who are perceived as being too slim, and overweight children who are perceived as having a healthy weight. 14 Studies on the perception of the child's weight show that identification of overweight in offspring is commonly underestimated by mothers.…”
Section: Introductionmentioning
confidence: 99%